Effect of Thermal Quantum Species Screening Around Fuel Cell Anode Performance - Dhobi, Saddam Husain; Nakarmi, Jeevan Jyoti; Gupta, Suresh Prasad; Yadav, Kishori; Jha, Ajay Kumar (Journal of Nepal Physical Society, 2024)
The objective of this work is to develop a theoretical model, to study the effect of quantum species, activation potential, current density, and temperature on the performance of Pt/C catalysts in Proton Exchange Membrane Fuel Cells (PEMFCs). For this we modified Butler-Volmer equations and analyzing I-V characteristics, the observation shows lower activation potential of 40 mV yields better performance compared to 55 mV. The effect of temperature was observed showing that increased in temperatures can mitigate carbon support corrosion and decline the performance of PEMFCs. Also increasing the electron flow per reaction cycle decrease the performance of PEMFCs by screening the flow of electron by quantum species formed around anode of PEMFCs. This result bring negative voltage and power, highlighting the complex interplay between these factors. The results underscore the importance of optimizing activation potential and managing temperature to enhance PEMFCs performance and longevity.